Utilization of fly ash-derived HZSM-5: catalytic pyrolysis of Jatropha wastes in a fixed-bed reactor. Issue 13 (18th July 2017) - Vichaphund, S.; Sricharoenchaikul, V.; Atong, D.
ABSTRACT: Fly ash-derived HZSM-5 catalyst was first applied in the catalytic pyrolysis of Jatropha residues in a semi-continuous fixed-bed reactor. The catalytic performance of HZSM-5 catalysts prepared from chemicals including conventional hydrothermal HZSM-5, Ni/HZSM-5 by ion exchange, and commercial HZSM-5 (Si/Al = 30) was evaluated for comparison. Catalytic pyrolysis of Jatropha residues with HZSM-5 catalysts was investigated in terms of product yields and qualities of bio-oil and bio-char. The liquid yield produced from fly ash-derived HZSM-5 was 29.4%, which was comparable to those obtained from chemicals and commercial (30.2–32.2%). Fly ash-derived HZSM-5 had high efficiency in increasing desirable compounds such as aliphatics and phenols as well as decreasing oxygenates and particularly N-containing compounds in bio-oils. The higher heating values and pH value of catalytic bio-oil achieved from fly ash-derived HZSM-5 were comparable to those achieved from HZSM-5 prepared from chemicals and commercial. The bio-char had 48–50 wt% carbon and was classified as mesoporous material. Overall, HZSM-5 derived from fly ash showed potentials to use as a catalyst for catalytic pyrolysis application.